Identiﬁcation of the strength of junction coupling eﬀects in water hammer - Riedelmeier, Stefan; Becker, Stefan; Schlücker, Eberhard (Journal of Fluids and Structures, 2017)
In order to analyse the eﬀects of junction coupling during water hammer in piping systems, a test facility has been designed and constructed. The main objective is to identify the dependence on the bend geometry and the strength of two-way coupling, and to derive a critical, geometric parameter, by means of which it is easily evaluated whether signiﬁcant two-way eﬀects occur or not. Oscillation experiments on movable U-shaped bends with various geometries were carried out. The excitation was realised by water hammer. The bend conﬁgurations diﬀered in distance between the parallel levers, which results in diﬀerent excitation forces, masses and stiﬀnesses. Inter alia the vertical displacement of the bend and the pressure inside the pipe were measured for various free oscillating lengths while the rest of the piping system was restrained. The results are displayed in curves of the maximum displacement and frequency spectra of the pressure and the displacement for the diﬀerent bend conﬁgurations. Additional experiments with variable excitation at the coincidence frequency for two bend conﬁgurations were performed. Only for the medium and long bend conﬁgurations, two-way junction coupling eﬀects were resolved. The strength of the coupling was found to be independent of the excitation, which just scaled the amplitudes. A quantiﬁcation of the strength of the two-way coupling eﬀects was performed by an analogy with the two-mass oscillator. This method was veriﬁed using coupled simulations. Owing to the good agreement between the results of the experiments and the simulations, additional bend conﬁgurations were calculated. Using this data, it is possible to evaluate the strength of the coupling on the basis of the geometry and mass of the bend.
Keywords: FSI Junction coupling; Oscillation Two-mass oscillator; Water hammer